2013
DOI: 10.1093/annonc/mdt303
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing the treatment of women with early breast cancer: highlights of the St Gallen International Expert Consensus on the Primary Therapy of Early Breast Cancer 2013

Abstract: The 13th St Gallen International Breast Cancer Conference (2013) Expert Panel reviewed and endorsed substantial new evidence on aspects of the local and regional therapies for early breast cancer, supporting less extensive surgery to the axilla and shorter durations of radiation therapy. It refined its earlier approach to the classification and management of luminal disease in the absence of amplification or overexpression of the Human Epidermal growth factor Receptor 2 (HER2) oncogene, while retaining essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
2,603
3
105

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 3,104 publications
(2,882 citation statements)
references
References 97 publications
34
2,603
3
105
Order By: Relevance
“…Classification of molecular subtypes was based on St Gallen recommendations14 with IHC analysis of ER, PR and Ki‐67, and silver ISH analysis of HER2. The molecular subtypes were defined as follows: luminal A‐like (ER‐positive and PR more than 20 per cent, low Ki‐67 and HER2‐negative), luminal B‐like HER2‐negative (ER‐positive, PR 20 per cent or less and/or high Ki‐67 and HER2‐negative), luminal B‐like HER2‐positive (ER‐positive and/or PR‐positive, any Ki‐67 and HER2‐positive), HER2‐positive (non‐luminal) (ER‐negative, PR‐negative, any Ki‐67 and HER2‐positive) and triple‐negative (ER‐negative, PR‐negative, HER2‐negative, any Ki‐67).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Classification of molecular subtypes was based on St Gallen recommendations14 with IHC analysis of ER, PR and Ki‐67, and silver ISH analysis of HER2. The molecular subtypes were defined as follows: luminal A‐like (ER‐positive and PR more than 20 per cent, low Ki‐67 and HER2‐negative), luminal B‐like HER2‐negative (ER‐positive, PR 20 per cent or less and/or high Ki‐67 and HER2‐negative), luminal B‐like HER2‐positive (ER‐positive and/or PR‐positive, any Ki‐67 and HER2‐positive), HER2‐positive (non‐luminal) (ER‐negative, PR‐negative, any Ki‐67 and HER2‐positive) and triple‐negative (ER‐negative, PR‐negative, HER2‐negative, any Ki‐67).…”
Section: Methodsmentioning
confidence: 99%
“…High expression levels of the proliferation marker Ki‐67 are related to poor prognosis12. According to the St Gallen 2011 and 2013 guidelines13, 14, a proxy for the molecular subtype classification based on immunohistochemical analysis and in situ hybridization (ISH) of ER, PR, Ki‐67 and HER2 can be used to divide tumours into four to five main subtypes: luminal A‐like, luminal B‐like (HER2‐positive or HER2‐negative), HER2‐positive (non‐luminal) and triple‐negative breast cancer. This classification is important as it provides prognostic information that guides systemic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a larger cohort of breast cancer patients revealed that the luminal subgroup may be divided into luminal A and B 29. Luminal B was previously shown to have a more aggressive phenotype, higher HG, and more proliferative index such as Ki67 than luminal A 30, 31, 32. The prognosis of patients with luminal B tumors was also found to be worse than those with luminal A tumors despite treatments with hormonal therapy 33.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer subtypes were defined to histopathological characteristics such as receptor status and grading according to the St. Gallen classification and by von Minckwitz and colleagues (Goldhirsch et al ., 2013; von Minckwitz et al ., 2012). …”
Section: Methodsmentioning
confidence: 99%